Association of prefabricated metal post with the method of removal - a retrospective study - BASKAR, KEERTHANA; ANTONY, DELPHINE PRISCILLA; DHARMAN, SREEDEVI (The journal of contemporary issues in business and government, 2021)
Removal of post forms an integral part of endodontic retreatment. The aim of this study is to evaluate the association between prefabricated metal post and the method of post retrieval. A study of sample size eight was conducted of patients who had undergone metal post retrieval. Excel calculation was done, analysed and transferred to SPSS for statistical analysis. The p value was set at 0.05. From this study, it is observed that mechanical method of removal of posts was commonly practised (62.5%). Ultrasonic removal of prefabricated metal posts was performed in 37.5%. Post removal in 22 was done with ultrasonics as well as mechanically in equal numbers. Removal of post in 12 was done solely with ultrasonics. Within the limits of the study, mechanical removal of post has been done predominantly in the upper and lower central incisors. Ultrasonic removal of post is done solely in the lateral incisor in the present study.